Direct transatrial pericardiocentesis for tamponade caused by left atrial perforation after trans-septal puncture. (7th July 2016) - Picard, Fabien; Millán, Xavier; de Hemptinne, Quentin; L L'allier, Philippe
Abstract : Trans-septal puncture is associated with risks of serious complications. We report a case of an obese 52-year-old man with hypertrophic cardiomyopathy who underwent preoperative coronary angiography and cardiac catheterisation complicated by left atrial perforation. We describe a direct transatrial pericardiocentesis approach to treating cardiac tamponade.